Thomas Jefferson: The Fight Against Slavery - Pirzadeh, Hannah Brooke (URJ-UCCS: Undergraduate Research Journal at UCCS, 2017)
Thomas Jefferson's views on slavery were controversial in his time, and often misunderstood in the world today. Jefferson was clear however; he opposed the institution of slavery. Through political documents, decrees, laws, and personal correspondence, he made his opposition to slavery clear.